Revisiting glaciological measurements on Haupapa/Tasman Glacier, New Zealand, in a contemporary context - Purdie, Heather; Anderson, B; Mackintosh, A; Lawson, W (Geografiska Annaler: Series A, Physical Geography, 2018)
Compilation of fragmented glaciological data, spanning more than a century at Haupapa/Tasman Glacier, provides new insight on how this glacier is changing over time. Despite consistency in high accumulation on the glacier, dramatic surface thinning and up-glacier expansion of supraglacial debris highlights that the glacier is currently in disequilibrium with climate. However, pauses in the rate of debris emergence indicate that despite ongoing terminus retreat at the proglacial lake, a subtle response to climate is still detectable mid-glacier. Analysis of surface velocity data at key locations reveals no trend over time at the Malte Brun site in the upper ablation area, but recent deceleration was recorded near the Ball Glacier confluence, located 5 km up-glacier from the current terminus. Near-terminus acceleration during a period of rapid lake expansion, followed by more recent deceleration, demonstrates that at this time, ice thinning at Haupapa/Tasman Glacier is likely being driven by negative surface mass balance as opposed to dynamic thinning associated with proglacial lake enlargement.